From Solid‐Solution Electrodes and the Rocking‐Chair Concept to Today's Batteries. (12th December 2019) - Zhang, Heng; Li, Chunmei; Eshetu, Gebrekidan Gebresilassie; Laruelle, Stéphane; Grugeon, Sylvie; Zaghib, Karim; Julien, Christian; Mauger, Alain; Guyomard, Dominique; Rojo, Teófilo; Gisbert‐Trejo, Nuria; Passerini, Stefano; et al.
Abstract: Lithium‐ion batteries (LIBs) have become ubiquitous power sources for small electronic devices, electric vehicles, and stationary energy storage systems. Despite the success of LIBs which is acknowledged by their increasing commodity market, the historical evolution of the chemistry behind the LIB technologies is laden with obstacles and yet to be unambiguously documented. This Viewpoint outlines chronologically the most essential findings related to today's LIBs, including commercial electrode and electrolyte materials, but furthermore also depicts how the today popular and widely emerging solid‐state batteries were instrumental at very early stages in the development of LIBs. Abstract : Geschwisterrivalität : Dieser Standpunkt präsentiert die essentiellsten Erkenntnisse in Bezug auf moderne Lithium‐Ionen‐Batterien (LIBs) und Festkörper‐Batterien (SSBs), liefert einen historischen Überblick, zeigt fundamentale chemische Erwägungen auf und demonstriert, wie entscheidend die nun aufstrebenden SSBs in der Anfangsphase der Entwicklung von LIBs waren.